User experience design for mixed reality: a case study of HoloLens in museum. (20th January 2020) - Hammady, Ramy; Ma, Minhua; Strathearn, Carl
In recent years, the applications of mixed reality (MR) processing have become highly apparent in academia and the manufacturing industry with the release of innovative technologies such as the Microsoft HoloLens. However, crucial design issues with the HoloLens' restricted field of view (FOV) to a narrow window of 34 degrees inhibited the user's natural peripheral vision (Kress and Cummings, 2017). This visual limitation results in a loss of pre-set functions and projected visualisations in the AR application window. This paper presents an innovative methodology in designing a spatial user interface (UI), to minimise the adverse effects associated with the HoloLens' narrow FOV. The spatial UI is a crucial element towards developing a museum-based MR system, which was evaluated by nine experts in human-computer interaction (HCI), visual communication and museum studies. Results of this study indicate a positive user reaction towards the accessibility of the spatial UI system and enhancing the user experience. This approach can help current and future HoloLens developers to extend their application functions without visual restrictions and missing content.